Optimalisasi Pengelolaan Sampah Plastik Serta Pemberdayaan Masyarakat Dalam Peningkatan Ekonomi Warga Dusun Semingkir Purwokerto - Bachrul Restu Bagja; Luqman Wahyudi; Yanuar Ikhsan Pamuji; Yohani Setiya Rafika Nur (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Covid-19 has left many traces on the Indonesian people, the sorrow of losing family, friends and relatives, as well as the consumer behavior of society. Behavior during the pandemic then becomes a new habit for society, where purchases of goods, food or drinks online continue to be made. This has an impact on the increasing amount of household waste, there is a buildup of waste, especially plastic-based waste. Plastic waste is a type of waste that poses a serious threat to the environment because it is not easily decomposed by nature. Destruction of plastic waste through burning also creates new problems in the form of air pollution which increases the risk of cancer. Public awareness of the negative impacts of plastic waste is increasing in big cities and in regions, such as Banyumas Regency, one of which is encouraged by the existence of a non-governmental group that is engaged in utilizing waste, namely the Inyong Waste Bank. Conventional methods in processing waste, product distribution patterns and management that are not optimal have caused the public's interest in getting involved in the Inyong Waste Bank to decrease because the economic value has decreased drastically. There are solutions in the form of increasing capabilities in processing waste using alternative methods, public interest in managing the Inyong Waste Bank, as well as arranging new distribution patterns so that they can increase the economic value of products resulting from periodic training activities with outputs in the form of websites, logo designing and product innovation and promotion training.